Physiological Acclimation of Lessonia Spicata to Diurnal Changing Par and Uv Radiation: Differential Regulation Among Down-Regulation of Photochemistry, Ros Scavenging Activity and Phlorotannins as Major Photoprotective Mechanisms - Arancibia-Miranda, N; Arancibia-Miranda, N (Springer Netherlands, 2017)
Intertidal macroalgae are constantly subjected to high variations in the quality and quantity of incident irradiance that can eventually generate detrimental effect on the photosynthetic apparatus. The success of these organisms to colonize the stressful coastal habitat is mainly associated with the complexity of their morphological structures and the efficiency of the anti-stress mechanisms to minimize the physiological stress. Lessonia spicata (Phaeophyceae), a brown macroalga, that inhabits the intertidal zone in central–southern Chile was studied in regard to their physiological (quantum yield, electron transport rate, pigments) and biochemical (phlorotannins content, antioxidant metabolism, oxidative stress) responses during a daily light cycle under natural solar radiation. Major findings were that Fv/Fm, photosynthetic parameters (ETRmax, alpha, Ek) and pigments in L. spicata showed an inverse relationship to the diurnal changes in solar radiation. Phlorotannins levels and antioxidant activity showed their highest values in treatment that included UV radiation. There was an increase in SOD and APX in relation at light stress, with a peak in activity between 5.2 and 10.1 W m−2 of biologically effective dose. The increase in peroxidative damage was proportional to light dose. These results indicated that different light doses can trigger a series of complementary mechanisms of acclimation in L. spicata based on: (i) down-regulation of photochemistry activity and decrease in concentration of photosynthetic pigments; (ii) induction of phenolic compounds with specific UV-screening functions; and (iii) reactive oxygen species (ROS) scavenging activity via complementary repair of the oxidative damage through increased activity of antioxidant enzymes and potentially increased amounts of phenolic compounds. © 2016, Springer Science+Business Media Dordrecht.